Management and outcome of cardiogenic shock complicating acute myocardial infarction in hospitals with and without on-site catheterisation facilities. Issue 2 (1st August 2001) - Barbash, I M; Behar, S; Battler, A; Hasdai, D; Boyko, V; Gottlieb, S; Leor, J
Abstract : OBJECTIVE: To determine whether the availability of on-site catheterisation and revascularisation facilities influenced hospital management and outcome of patients with acute myocardial infarction complicated by cardiogenic shock. METHODS: Patients with acute myocardial infarction were enrolled prospectively in four nationwide surveys during 1992, 1994, 1996, and 1998. The characteristics, management, and outcome of patients with cardiogenic shock were compared between hospitals with on-site catheterisation facilities (group 1; 18 hospitals) and without such facilities (group 2; 8 hospitals). RESULTS: Of 5351 patients with acute myocardial infarction, 254 (4.7%) developed cardiogenic shock. Group 1 patients (n = 186 of 3854; 4.6%) were younger (mean (SD) age, 69.6 (12) v 73.7 (10) years, p = 0.006) and had a lower proportion of women (36% v 52%, p = 0.03) than group 2 (n = 68 of 1243; 5.2%). There was no difference in other characteristics including the use of thrombolysis. Group 1 patients more often underwent coronary angiography (26% v 4%, p < 0.001), angioplasty (21% v 4%, p = 0.002), and intra-aortic balloon counterpulsation (28% v 4%, p < 0.001). Seven day mortality was lower among group 1 than among group 2 patients (61% v 77%, p = 0.02), even after age and sex adjustment (odds ratio (OR) 0.54; 95% confidence interval (CI) 0.28 to 1.02). This outcome benefit persisted at 30 days (74% v 88%, p = 0.01; OR 0.45, 95% CI 0.18 to 0.98), and at 6 months (80% v 90%, p = 0.06; OR 0.57, 95% CI 0.22 to 1.33). CONCLUSIONS: The greater use of invasive and interventional procedures in hospitals with catheterisation facilities is associated with improved survival of patients with acute myocardial infarction complicated by cardiogenic shock. Immediate availability of invasive care facilities will improve the outcome of cardiogenic shock in the community setting.